Determinants and prognostic impact of afterload mismatch after MitraClip implantation. (3rd October 2022) - Angelini, F; Pidello, S; Frea, S; Bocchino, P; Boretto, P; Gravinese, C; Mandurino Mirizzi, A; Masiero, G; Montonati, C; Biasco, L; Pighi, M; Giannini, F; et al.
Abstract: Introduction: Mitral transcatheter edge-to-edge repair (TEER) is a widespread option to treat mitral regurgitation in high-risk patients. The sudden reduction of mitral regurgitation (MR) following TEER abruptly eliminates the low-impedance regurgitant flow into the left atrium, leading to an increase in left ventricle (LV) afterload with possible impairment of LV systolic function, defined afterload mismatch (AM). Purpose: To explore a new definition of AM and to analyze the determinants and prognostic role of AM in patients with functional MR (FMR) undergoing TEER. Methods: This was an international multicenter case-control study including adult patients with severe FMR and LVEF ≤35% undergoing TEER between 2012 and 2020. AM was defined as the acute need to initiate or increase inotropic support by a vasoactive inotropic score ≥3 or the need for a mechanical circulatory support following TEER. Results: 80 patients with AM were compared to 80 consecutive patients undergoing TEER not meeting the criteria for AM. Median age was 67 years, 79% of patients were male, had a median LVEDV of 240 ml with severely reduced LVEF (median 26%) and pulmonary hypertension (median 48 mmHg). Median EROA/LVEDV ratio was 0.17 (IQR 0.12–0.24) based on which 37% of the total population presented with proportionate MR. Levosimendan was administered before TEER in 42% of patients while intravenous vasodilators in 43%. In most patients more than 1 clip were needed (2 clips in 88 patients, 3 clips in 11). Patients presenting AM more commonly had a lower EROA/LVEDV ratio (0.14 vs. 0.18, p<0.001) leading to a higher percentage of patients with proportionate MR (55% vs. 22%, p<0.001; Figure 1) and had more clips implanted (p=0.008). AM was graded as mild in 74% of patients, moderate in 15% and severe in 11%. At multivariate analysis, patients with proportionate MR were more likely to develop AM after TEER (OR 2.95, 95% CI: 1.32–6.60, p=0.008), while those treated with levosimendan (OR 0.32, 95% CI: 0.15–0.71, p=0.005) and/or IV vasodilators (OR 0.44, 95% CI: 0.21–0.96, p=0.040) before TEER were less likely to suffer from AM. In-hospital death occurred in 7 cases, all being part of AM group. Patients were more likely to die in-hospital if AM was more severe (OR 2.56, 95% CI: 1.19–5.54, p=0.017), and for higher grades of residual MR (OR 3.35, 95% CI: 1.27–8.79, p=0.014). The 2-year survival rate did not differ significantly between groups (66% vs 75%, HR 1.51, 95% CI: 0.73–3.12, p=0.270; Figure 2). At 2 years 51 patients (32%) were re-hospitalized for HF, independently from post-procedural AM (HR 1.36, 95% CI: 0.70–2.67, p=0.363). Conclusions: In patients with LVEF ≤35% and severe FMR undergoing TEER, the development of AM predicted in-hospital mortality, while long-term outcomes were not affected by acute AM. The use of levosimendan or intravenous vasodilators during the pre-procedural phase reduced the risk of acute AM. Funding Acknowledgement: Type of funding sources: None.